2017
DOI: 10.3390/genes8110336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bifidobacterium Species Using groEL Gene on the Basis of Illumina MiSeq High-Throughput Sequencing

Abstract: The next-generation high-throughput sequencing techniques have introduced a new way to assess the gut’s microbial diversity on the basis of 16S rRNA gene-based microbiota analysis. However, the precise appraisal of the biodiversity of Bifidobacterium species within the gut remains a challenging task because of the limited resolving power of the 16S rRNA gene in different species. The groEL gene, a protein-coding gene, evolves quickly and thus is useful for differentiating bifidobacteria. Here, we designed a Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…This appears to be the first description of the composition of Bifidobacterium in mice. Hu et al [ 15 ] found that the predominant Bifidobacterium species were B. pseudocatenulatum , B. adolescentis , and B. longum in adult human feces, while the dominant species in the gut of rats was B. animalis (>90%), suggesting that the composition of Bifidobacterium varies substantially among different hosts. It is well known that FOS can selectively stimulate the growth of bifidobacteria in hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This appears to be the first description of the composition of Bifidobacterium in mice. Hu et al [ 15 ] found that the predominant Bifidobacterium species were B. pseudocatenulatum , B. adolescentis , and B. longum in adult human feces, while the dominant species in the gut of rats was B. animalis (>90%), suggesting that the composition of Bifidobacterium varies substantially among different hosts. It is well known that FOS can selectively stimulate the growth of bifidobacteria in hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR conditions were 95 °C for 5 min; 95 °C for 30 s, 52 °C for 30 s, 72 °C for 30 s, repeat for 30 cycles; and 72 °C for 10 min. To distinguish the species within the genus Bifidobacterium , the groEL gene was amplified with the primers Bif-groEL-F (5′-TCC GAT TAC GAY CGY GAG AAG CT-3′)/Bif-groEL-R (5′-CSG CYT CGG TSG TCA GGAACA G-3′) [ 15 ]. The bacterial genome was set as the template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer (CRC) is one of the most common forms of cancer [75]. High-calorie diets, rich in animal fat, red and processed meat or alcohol, and low in dietary fiber, whole grains and vegetables are considered a main risk factor [75,76]. Gut microbiota structure and function is largely dependent on diet, and certain bacterial metabolites are known to be proinflammatory and tumor inducing.…”
Section: Selected Diseases Associated With Dysbiosis Of the Intestinamentioning
confidence: 99%
“…In addition, identification of species or strains is not reliable [74]. Species-specific primer pairs targeting a hypervariable sequence of a fast evolving gene can be used instead, or in addition to universal primers to provide information about specific species or strains [24,75]. Other approaches have been developed recently that have the potential to provide a better resolution of the sequencing data by generating sequencing reads which span nearly the entire length of the 16S rRNA gene [76], and also do not require PCR amplification, thus avoiding a primer bias [77].…”
Section: Future Perspectivesmentioning
confidence: 99%